Pengaruh Penambahan Kacang Merah, Ampas Kedelai, dan Textured Vegetable Protein pada Kandungan Nutrisi dan Tekstur Daging Sapi Sintetik - Dewi Tristantini; Angela Susanti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
As beef consumption can increase risk of cancer and cardiovascular disease, an alternative food in the form of synthetic beef which contains important nutrients with less health risk can be made. In this research, protein content will be derived from gluten, kidney bean, soy pulp, and textured vegetable protein which are varied in concentration. Our results indicated that increase of kidney bean flour and textured vegetable protein will increase ash, protein, and fat content while increase of soy pulp will increase water and carbohydrate content, decrease the amount of calories, and reduce synthetic beef’s hardness. The best synthetic beef has been made with a combination of 60% gluten, 10% kidney bean flour, 20% soy pulp, and 10% textured vegetable protein. According to proximate and calorimetry analysis, the best synthetic beef contained 60.3% water, 0.6% ash, 19.3% protein, 4.5% fat, 15.6% carbohydrate, and 178 kal/100 g. According to texture profile analysis, the best synthetic beef had 0.570 cohesiveness, 5845.4 gf hardness, and 88.0 springiness. Synthetic beef has similar cohesiveness and elasticity but higher hardness than beef. Based on this research, synthetic beef with sufficient amount of nutrient and less health risk has been produced.